Complement receptor 2 (CR2/CD21) - Dash, Rozaleen; Das, Nibhriti (International Journal of Research in Medical Sciences, 2017)
Human complement receptor type 2 (CR2/CD21) is a surface-associated glycoprotein which binds to a variety of endogenous ligands, including the complement component C3 fragments iC3b, C3dg and C3d, the low-affinity IgE receptor CD23, and the type I cytokine, interferon-alpha. This receptor serves as an important interface between the complement system and adaptive immunity. It is expressed on B-lymphocytes, follicular dendritic cells, some epithelial cells, peripheral blood T cells. CR2 also play an important role in enhancing humoral immunity to T-dependent and T-independent foreign antigens and in regulating T-cell immunity to self and non-self-antigens. It is an important receptor that amplifies B lymphocyte activation by bridging the innate and adaptive immune systems. CR2 ligands include complement C3d and Epstein-Barr virus glycoprotein 350/220. Regions of EBV have structural similarity to C3dg, which allows it to bind CR2, and thereby gain access to cell’s interior. It also acts as receptor for other components or activators of innate immunity such as IFN-α, an anti-viral cytokine and DNA-DNA containing complexes such as chromatin. The binding of CR2 to IFN-α is speculated to cause B cell activation but their roles are still not clear. Variations or deletions of the CR2 gene in humans, or the Cr2 gene in mice associate with a variety of autoimmune and inflammatory conditions.